2021
DOI: 10.3390/cells10040906
|View full text |Cite
|
Sign up to set email alerts
|

Induced Torpor as a Countermeasure for Low Dose Radiation Exposure in a Zebrafish Model

Abstract: The development of the Artemis programme with the goal of returning to the moon is spurring technology advances that will eventually take humans to Mars and herald a new era of interplanetary space travel. However, long-term space travel poses unique challenges including exposure to ionising radiation from galactic cosmic rays and potential solar particle events, exposure to microgravity and specific nutritional challenges arising from earth independent exploration. Ionising radiation is one of the major obsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 154 publications
(172 reference statements)
2
10
1
Order By: Relevance
“…FDR is the expected fraction of false positive tests among significant tests and was calculated using the Benjamini-Hochberg multiple testing adjustment procedure. Differentially expressed genes (DEGs) were defined by q-value < 0.05 and log2FC > 0.6 for upregulated DEGs, and log2FC < −0.6 for downregulated DEGs [96,97].…”
Section: Rna Sequencing and Differential Expression Analysismentioning
confidence: 99%
“…FDR is the expected fraction of false positive tests among significant tests and was calculated using the Benjamini-Hochberg multiple testing adjustment procedure. Differentially expressed genes (DEGs) were defined by q-value < 0.05 and log2FC > 0.6 for upregulated DEGs, and log2FC < −0.6 for downregulated DEGs [96,97].…”
Section: Rna Sequencing and Differential Expression Analysismentioning
confidence: 99%
“…On the other hand, our results showed that exposure to low-dose radiation caused DNA damage, oxidative stress, glucocorticoid signalling, and cell cycle arrest. When irradiated under induced/synthetic torpor, radiation-induced stress signals were observed, however, the increase in anti-apoptotic, mitogenic, and pro-survival signals were all maintained, suggesting radio-protective effects 37 . Here we report our findings in the context of hepatic health.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, we used investigated in vitro to clarify the mechanism of radioresistance. It has been argued that the lower concentration of oxygen in the tissues of an animal in synthetic torpor could be a relevant factor in preventing cell damage by radiation-induced ROS 24 . Furthermore, changes in the metabolism at low temperature may also have an impact on DNA repair 25 .…”
Section: Introductionmentioning
confidence: 99%